Impact of Prolonged Mobile Phone and Digital Device Use on Visual Symptoms and Ocular Surface Health among patients attending the Ophthalmology Clinic at Swat Medical Complex and Teaching Hospital - Nawab Ali Khan, Abshar Ahmad, Jamal Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The widespread use of mobile phones and digital devices has increased concerns regarding their potential impact on ocular health. Prolonged screen exposure may lead to visual symptoms and disturbances of the ocular surface. Objective: To evaluate the impact of prolonged mobile phone and digital device use on visual symptoms and ocular surface health among patients attending an ophthalmology clinic. Methods: This was a hospital-based descriptive cross-sectional study conducted at Swat Medical Complex Teaching Hospital from May 2022 to May 2023including 220 patients attending the ophthalmology clinic. Results: The mean age of participants was 29.8 ± 10.6 years with an average screen time of 6.4 ± 2.1 hours per day. Smartphones were the most commonly used devices (62.7%). Eye strain was reported by 57.3% of participants, dryness by 44.5%, headache by 41.4%, and blurred vision by 33.6%. The mean tear break-up time was 8.9 ± 3.2 seconds, and reduced tear production was observed in 41.8% of participants. Clinical dry eye was diagnosed in 40.0% of cases. Conclusion: Prolonged digital device use is associated with a high frequency of visual symptoms and ocular surface abnormalities. Preventive measures such as limiting screen exposure, taking regular breaks, and promoting safe digital habits may help reduce digital eye strain and improve ocular health. Keywords: Digital eye strain; Mobile phone use; Computer vision syndrome; Ocular surface health; Dry eye disease